SIFO 1990: Splitted Swedes for the EC - Swedish Institute of Public Opinion Research; Swedish Employers´ Confederation (Swedish Institute of Public Opinion Research, 1994)
In this study, carried out by the Swedish Institute of Public Opinion Research (SIFO) at the request of the Swedish Employers´ Confederation, the respondents were asked about their interest to follow what happens within the EC and Eastern Europe respectively; time for a Swedish EC-membership; conversations about the EC lately; the Swedish situation if not an EC-member; opinion on the development of standard of living, social welfare, and number of jobs if Sweden joins the EC; attitudes toward the free labour market within the EC and the right of people from other EC-countries to buy real estate in Sweden, and how a Swedish EC-membership would affect fields such as the working environment, food prices, equality and the security of the country. Background variables include information on gender, place of living, age, Swedish citizenship, occupation, private or public sector, trade union and income.

Denna studie, utförd av SIFO på uppdrag av Svenska Arbetsgivareföreningen (SAF), ställer frågor om respondenternas intresse att följa med vad som händer inom EG respektive Östeuropa, samt om den egna inställningen till en svensk ansökan om EG-medlemskap. Respondenten fick ange tidpunkt för ett troligt svenskt medlemskap i EG; om man samtalat med någon om EG under senaste tiden; inställning till att son eller dotter skulle arbeta i europeiskt land utanför Norden; Sveriges situation om man står utanför EG; tänkbara egna aktiviteter för ett svenskt EG-medlemskap; ett svenskt EG-medlemskaps inverkan på utvecklingen av levnadsstandarden, sociala välfärden och antalet jobb i Sverige. Andra frågor berörde inställningen till den fria arbetsmarknaden inom EG; till att människor från andra europeiska länder får rätt att köpa fastigheter och mark i Sverige; och hur arbetsmiljön, matpriserna, jämställdheten och landets säkerhet skulle påverkas av ett EG-medlemskap. Bakgrundsvariablerna innehåller information om kön, bostadsort, ålder, medborgarskap, yrke, arbete i privat eller offentlig sektor, medlemskap i fackförening och inkomst.
SIFO 1990: Kluvna svenskar positiva till EG
Keywords: european union; europeiska unionen; european integration; europeisk integration; internal politics; inrikespolitik; International politics and organisations; Internationell politik och organisationer; Social Sciences; Samhällsvetenskap